FAKTOR DETERMINAN YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA DENGAN MENGGUNAKAN PENDEKATAN THEORY PLAN BEHAVIOR - Sugiharti, Sugiharti (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
The purpose of this study was to analyze the magnitude of the influence of attitude, subjective norm, and perceived behavior control to entrepreneurial intention. The data in this study were obtained from student at STIE Totalwin Semarang. Results and the theoretical implications of this research is that this study supports previous research that says that the attitude, subjective norm, and perceived behavior control affect to entrepreneurial intention.